QR code security authentication attendance system - Lee, Wai Seng (Nanyang Technological University, 2023)
Quick Response ( QR ) Code technology – a two-dimensional code that evolved from the conventional bar code. QR technology was first utilized in industrial settings where industrial scanners scan and keep track of specific stages of production on the automobile assembly line. With the advent of customer technologies such as “do-it-all” super app (eg.TaoBao and Grab), the incorporation of QR codes made payment easier as every unit of smartphone can be a QR scanner. The equivalent of a handheld QR scanner in every pocket, the use of QR has now completely permeated our society and has been widely adopted by diverse sectors such as: healthcare, banking, logistics, and business operations. Incorporating QR Code technology for attendance tracking is a wise choice given its increasing popularity and ease of use. For this Final Year Project, the QR code technology will be incorporated into an attendance tracking application to be used in a university setting. This report reviews all the software involved in this attendance taking application, including Microsoft Visual Studio, Android Studio Android Emulator, MySQL, Apache and Google Chart Infographics. The system developed in this project comprises of 3 components: a webpage for the professors which acts as the QR code generator, a mobile application for the students to scan the QR code generated by the webpage, and a real-time database that links the mobile application and the webpage to function properly. Firstly, the QR code generated by the webpage used by the professor encapsulates class information and a unique numerical code using the Google Chart Infographics software. Secondly, the QR code scanner on the mobile application used by the students can decode the QR code to retrieve the necessary data to authenticate the scanned QR code. None of these functions would be successful without a real-time database. By leveraging a real-time database, the unique numerical code generated by the webpage can be rapidly stored in the database system for the mobile app to validate. Upon successful validation, the timestamp will be recorded as the user's check-in time and attendance record. In conclusion, the development of this application system will bring about huge time savings and efficiency at low cost. Now, more time and resources can be spent teaching and learning rather than in mundane administrative affairs.